Actual Arabic loan-words of religious content (on the material of modern foreign words) (Proceedings of Southern Federal University. Philology, 2015)
Application of thematic classification of actual vocabulary as a whole to the formation of loan words allows to see the uniqueness of seperate groups of the vocabulary. English loan words prevail relating to the sphere of economy, science and technology, loan words from Arabic dominate from the religious vocabulary.Application of field approach to the analysis of actual religious Arabisms revealed both nuclear and peripheral components of the field. At the core of the field there are such Arabisms as Allah and Islam, which can be characterized as key words. However, in unifying the features of these words vary at a number of parameters. The word Allah has zero derivation productivity and at lexicographical description (as opposed to functioning in the language of the media) is free of connotations. Arabism, Islam, by contrast, has a high derivation productivity and derived words can express evaluation. Lexicographic description of the Arabism Islam is also quite diverse stylistically and in contents.The core of the field “Muslim religion” also includes a number of words fixed in most modern dictionaries of foreign words.At the periphery of the field there are Arabisms that do not have high levels of frequency, but at the same time as an indicator of dominant Arabisms of religious content among topical Arabisms.Keywords: arabism, topical vocabulary, field, core, periphery, key words.Al Shammari Majid Jamil Ashur (Iraque) - post-graduate student of Russian language dpt. Institute of linguistics, journalism and cross-cultural communication, Southern federal university. E-mail: nawrc.aliraq@yahoo.com